2016
DOI: 10.1074/jbc.m116.750570
|View full text |Cite
|
Sign up to set email alerts
|

A Ribonucleoprotein Supercomplex Involved in trans-Splicing of Organelle Group II Introns

Abstract: In the chloroplast of the green alga Chlamydomonas reinhardtii, two discontinuous group II introns, psaA-i1 and psaAi2, splice in trans, and thus their excision process resembles the nuclear spliceosomal splicing pathway. Here, we address the question whether fragmentation of trans-acting RNAs is accompanied by the formation of a chloroplast spliceosome-like machinery. Using a combination of liquid chromatographymass spectrometry (LC-MS), size exclusion chromatography, and quantitative RT-PCR, we provide the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…It has been suggested that several group II intron splicing factors, such as CRM, PPR, APO, and PORR proteins, are present in a high molecular weight complexes in chloroplasts (0.5–1 MDa; Asakura et al , 2008; Hammani and Barkan, 2014; Reifschneider et al , 2016). Our results indicated that splicing of nad2 -introns 2 and 3 and nad5 -intron 1 was impaired in both ppr-smr1 and Zm-mcsf1 (Figs 2A, B, 4A, B, Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that several group II intron splicing factors, such as CRM, PPR, APO, and PORR proteins, are present in a high molecular weight complexes in chloroplasts (0.5–1 MDa; Asakura et al , 2008; Hammani and Barkan, 2014; Reifschneider et al , 2016). Our results indicated that splicing of nad2 -introns 2 and 3 and nad5 -intron 1 was impaired in both ppr-smr1 and Zm-mcsf1 (Figs 2A, B, 4A, B, Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Excision of the introns from the pre‐mRNAs and ligation of exons involve huge and highly dynamic ribonucleoprotein machine, the supraspliceosome (Reifschneider et al, ). We identified components of the supraspliceosome known to have both splicing and editing activities.…”
Section: Discussionmentioning
confidence: 99%
“…Both PRR9 and LWD1 are known to be involved in a positive feedback loop in Arabidopsis circadian clock(Wu et al, 2016). The identification of novel clock proteins and their phosphorylation status might provide missing pieces to the puzzle of photoperiod modulation.Excision of the introns from the pre-mRNAs and ligation of exons involve huge and highly dynamic ribonucleoprotein machine, the supraspliceosome(Reifschneider et al, 2016). We identified compo-nents of the supraspliceosome known to have both splicing and editing activities.…”
mentioning
confidence: 99%
“…Emerging evidence suggests several splicing factors reside in high molecular weight complexes in chloroplasts, which include CRM, PPR, APO, and PORR proteins (Asakura et al, 2008;Hammani and Barkan, 2014;Reifschneider et al, 2016). Our results showed that the inefficient splicing of nad2 intron 3 and nad7 intron 2 was found in both ppr14 and ppr-smr1 (Chen et al, 2019), and the inefficient splicing of nad2 intron 3 in ppr14 and Zm-mcsf1 (Chen et al, 2019).…”
Section: Ppr14 Interacts With Ppr-smr1 and Zm-mcsf1mentioning
confidence: 53%